Chronic intermittent hypoxia induces early-stage metabolic dysfunction independently of adipose tissue deregulation - Martins, Fátima O. (2021)
Funding Information: Funding: The present study was supported by grant reference BFU2015-70616-R (MINECO/FEDER; DGICYT), and VA106G18 (JCyL), Spain and by the Portuguese Foundation for Science and Technology with contracts for Fátima O. Martins (CEECIND/04266/2017) and Joana F. Sacramento (CEEC IND/02428/2018) and a PhD Grant for Bernardete F. Melo (PD/BD/128336/2017). Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.